Enzyme-responsive polycationic silver nanocluster-loaded PCL nanocomposites for antibacterial applications. (March 2023) - Uroro, E.O.; Bright, R.; Lakshika Dabare, P.R.; Quek, J.Y.; Goswami, N.; Vasilev, K.
Abstract: Infections caused by pathogenic bacteria such as Gram-positive Staphylococcus aureus and Gram-negative Pseudomonas aeruginosa remain a significant healthcare challenge . In this study, we developed an enzyme-responsive antibacterial nanomaterial that delivers antibacterial agents only in the presence of bacterial lipase. This was achieved by first synthesizing highly potent ultra-small silver nanoparticles with an average core size of 1.6 ± 0.2 nm and then embedding them into polycaprolactone nanoparticles (pAgNCs@PCL) via the water in oil in water approach. The pAgNCs@PCL nanoparticles had an average diameter of 274.1 ± 60.1 nm and a silver nanoparticle encapsulation efficiency of 15.7 ± 1.3%. We demonstrated that silver released from the pAgNCs@PCL was selectively triggered by lipase-expressing strains of P . aeruginosa and S. aureus . As expected, there was no antibacterial action observed against E. coli DH5α, which does not express lipase. The pAgNCs@PCL nanoparticles exhibited minimal cytotoxicity against human fibroblast cells suggesting good biocompatibility. This study resulted in a highly potent on-demand delivery system that can be potentially incorporated into healthcare products and devices to prevent and/or treat infections. Graphical abstract: Image 1 Highlights: The release of pAgNCs, was rapidly triggered by the presence of bacterial lipase. The pAgNCs loaded nanocomposites showed high antibacterial activity in lipase expressing bacteria. The on-demand release of the nanocomposite also contributed to the reduction of the pAgNCs cytotoxicity. The enzyme-responsive nanocomposites could be an attractive candidate for treating bacterial infections.